Analisis Faktor Penentu Kepesertaan Bpjs - Ismatut Thobibah; Ernawaty Ernawaty; Nyoman Anita Damayanti (Jurnal Keperawatan Silampari, 2020)
This study aims to analyze the relationship between information factors, knowledge, family support, and attitudes to become a member of the BPJS. The research method used was observational with a cross-sectional approach. The results showed that 69.4% were female, 32.2% were aged 36-45 years. 53.4% ​​have a high school education. The people who are members of the BPJS are 69.53%. There is a relationship between information about BPJS and BPJS membership (p-value = 0,000) and family support and attitudes to support BPJS, which are also related to BPJS membership (p-value = 0,000). Knowledge about BPJS is not related to BPJS membership (p-value = 0.229). In conclusion, information about BPJS, good family support, and a supportive attitude towards BPJS will determine BPJS membership, while knowledge is not related to BPJS membership. Keywords: Family Support, Information, BPJS Membership, Attitude